Balanced Scorecard Sebagai Kerangka Kerja Strategis dalam Meningkatkan Efisiensi Operasional - Neli Ferawati; Purwanti (GLOBAL SCIENTS PUBLISHER, 2025)
This study explores the role of the Balanced Scorecard (BSC) as a strategic framework in improving operational efficiency. Through a comprehensive literature review of relevant research published between 2019 and 2024, this study examines how BSC implementation affects various aspects of organizational performance. The findings indicate that BSC provides organizations with a more holistic approach to performance measurement by integrating four key perspectives: financial, customer, internal processes, and learning and growth. The research demonstrates that companies implementing BSC show significant improvements in internal process management, customer satisfaction, and employee development, leading to enhanced operational efficiency. Furthermore, organizations utilizing BSC are better positioned to adapt to market changes and maintain long-term sustainability through balanced consideration of both financial and non-financial metrics..